Three-Dimensional Modelling of Non-Linear Wave-Induced Seabed Response around Offshore Open-Ended Pile - Junwei Liu (MDPI AG, 2021)
This paper analyses the fluid–seabed–structure interactions (FSSI) around the open-ended pile by applying the in-house solver established on the open-source Computational Fluid Dynamics (CFD) platform. The Reynolds-averaged Navier–Stokes (RANS) equations are solved to simulate the hydrodynamic interactions between waves and open-ended piles. Biot’s poro-elastic theory (quasi-static model) is used to reproduce the wave-induced seabed responses. The parameter analysis indicates that the wave period, degree of saturation of seabed and pile diameter have a great influence on the development of the transient seabed liquefaction depth around the pile. In addition, the distribution of the pore water pressure vs soil depth in the inner zone of the pile presents a “V” shape rotated 90 degrees counterclockwise.